Electrospun Graphene Oxide/Poly(m-phenylene isophthalamide) Composite Nanofiber Membranes for High Performance - Enling Tian; Yinping Bi; Yiwei Ren (Membranes)
Due to its distinctive two-dimensional structure and high specific surface area, graphene oxide (GO) is expected to be a very promising material to be used for membrane separation. Not only can it improve the mechanical strength, surface wettability, and thermal stability of the membrane, but it can also improve the filtration performance and shelf life of the polymer membrane. Graphene oxide/poly(meta-phenylene isophthalamide) (GO/PMIA) nanofiber membranes were prepared by means of an electrospinning technique. The effects of adding different amounts of GO on the PMIA nanofiber membranes were studied. The results indicated that the GO had a strong affinity with the PMIA matrix by forming hydrogen bonds. The composite nanofiber membranes exhibited better filtration and thermostability performance than those of the pristine membrane. As the loading amount of GO was 1.0 wt%, the air filtration efficiency of the composite nanofiber membrane was 97.79%, the pressure drop was 85.45 Pa and the glass transition temperature was 299.8 °C.